Działalność Wyższej Szkoły Rzemieślniczej w Łodzi w przekazie „Dziennika Łódzkiego” pod koniec XIX wieku - Grzegorz Michalski, Grzegorz Michalski (Biuletyn Historii Wychowania, 2018)
The Technical Academy was established in Łódź in 1869. For many decades, it was the only occupational academy in the city. During a six-year’s course, it provided general education and educated specialists in textile studies and mechanics. As the activities of the institution largely revolutionized education of employees for the fast-developing industry and gradually gained more and more recognition among factory owners, “Dziennik Łódzki”, a newspaper published from 1884 to 1892, largely covered various aspects of the Academy’s operations. The newspaper presented the curriculum, listed all the subjects with the number of hours in a week and mentioned the mandatory apprenticeships in laboratories. It also provided information on mandatory internships in factories, specifying the names of the facilities. The newspaper published announcements on entry exams and described the celebrations of the end of the academic years. It also presented lists of graduates as well as information on school reunions. Information was published on a campaign of supporting poor students, including lifting the tuition fees, scholarships granted mainly by factory owners, or one-off cash support and free deliveries of student books, clothes, and shoes. “Dziennik Łódzki” also published information on two educational institutions operating at the Technical Academy, that is Sunday drawing courses for the labourers, junior foreman and technicians, and a four-year’s Sunday trading school for financial clerks.